Life cycle assessment of a farmed wood butanol-gasoline blend as an alternative transport fuel for passenger cars. (15th December 2021) - Feinauer, Mario; Ehrenberger, Simone; Buchgeister, Jens
Highlights: A novel well-to-wheel analysis of a biobutanol-gasoline fuel blend is performed. The fuel blend shows higher total environmental impacts than the fossil gasoline reference fuel. Steam production for the fuel blend causes higher emissions than gasoline production. Butanol lowers tailpipe emissions and environmental impacts in the fuel use stage. Abstract: The objective of this study is to investigate the environmental profile of farmed pine wood butanol blended with gasoline in a volumetric ratio of 30% and to compare the results with neat gasoline as a fossil reference fuel. To this end, the well-to-wheel approach has been chosen as it encompasses the entire fuel life cycle, i.e. the total fuel production chain including fuel use in the vehicle, while the vehicle manufacturing and infrastructure-related processes are excluded. The well-to-wheel analysis focuses on the biochemical production path in Germany for the years 2018 and 2040, considering different electricity generation mixes for the butanol production process and different fuel consumption and emission factors from passenger car operation in both years. The results, based on 16 midpoint impact categories of the ILCD2.0 life cycle impact assessment method, show that for the total fuel production and use stage, the butanol-gasoline blend has a higher environmental impact than the reference fuel. The main processes causing environmental impacts can be identified in the fuel production and related upstream stages. Regarding the use stage of the fuels, the butanol-gasoline blend reveals lower environmental impacts than the fossil gasoline reference fuel, as the biofuel blend reduces several tailpipe emission components like particulate matter. However, these reductions do not mitigate the total well-to-wheel impacts compared to fossil gasoline because fuel production and its upstream processes have a more significant impact. The analysis closes by highlighting several measures with a strong potential to improve the total environmental profile of the butanol-gasoline blend.